ANALYSIS OF MARKERS OF THE HEMOSTASIS SYSTEM IN PATIENTS WITH NON-VALVULAR ATRIAL FIBRILLATION WITH THROMBOEMBOLIC COMPLICATIONS - Marina Alexandrovna Dragunova; Ekaterina Sergeevna Sitkova; Oksana Nikolaevna Ogurkova; Roman Efimovich Batalov; Tatiana Evgenievna Suslova (Байкальский медицинский журнал)
Introduction. Atrial fibrillation (AF) is one of the most common heart rhythm disorders. The risk of developing thromboembolic complications, including ischemic stroke, in patients with AF is 5 times higher than that in patients with sinus rhythm; therefore, one of the main directions in the treatment of patients with this rhythm disorder is the prevention of thromboembolic complications.Objective: to study the markers of monitoring the blood coagulation system in the blood serum of patients with non-valvular AF receiving anticoagulant therapy and having a history of thrombotic and thromboembolic complications.Materials and methods. The study included 31 healthy volunteers (without a history of AF, thrombosis) and 31 patients over 18 years of age with a diagnosis of AF (mean age 66.2±8.1), receiving anticoagulant therapy and having a history of thrombotic and thromboembolic events. complications. Therapy taken by patients at the time of inclusion in the study was in line with current recommendations and included standard conventional antiarrhythmic and anticoagulant therapy, as well as therapy for the underlying cardiovascular disease. Biomarkers of thrombus formation and pro-inflammatory activation (L-selectin, thrombomodulin) were determined by enzyme immunoassay using diagnostic kits from BiomedicaGmbH, Austria.Results. During the screening of 2820 patients treated in the Department of CHLSRS&EX for the nosology of AF in the period 01.2020-01.2023, 31 patients were included in the study, who were diagnosed with thrombotic and thromboembolic complications (0.01% of the total number of screened patients) against the background of regular anticoagulant therapy . Among all patients included in the study, thrombotic complications in AF were as follows: thrombosis of the left atrial appendage was noted in 17 patients (54%), spontaneous echo contrast of grade II or more in 5 patients (16%), cardioembolic stroke - in 3 patients (10%) , thrombosis of peripheral arteries (2 (6%)), thrombosis on EKS electrodes (2 (6%)).The concentration of soluble thrombomodulin in the blood serum of patients with thrombotic and thromboembolic complications was reduced compared with the group of healthy volunteers (2073.0±548.6 vs. 2845.3±726.4 pg/ml; p=0.004).Serum levels of L-selectin in patients with thrombotic and thromboembolic complications were reduced compared to healthy volunteers (1.5±0.6 vs. 2.4±1.3 µg/mL; p=0.04).Conclusion. In patients with thrombotic and thromboembolic complications that occurred against the background of adequate anticoagulant therapy, there was a decrease in serum soluble thrombomodulin and L-selectin, which may indicate damage to the endothelium, activation of thrombus formation and inflammation.